Discussion on the pathogenesis of some types of jaundice, with special reference to hemolytic jaundice and Monge´disease - Urteaga Ballón, Oscar (1942)
The author discusses the pathogenic causes of certain types of Icterus, making special references to Hemolitic Icterus and Monqe's Disease. In human, as well as in experimental bartonellosis, a great erythrocyte destruction is noticeable, without any increase of blood bilirubin. He has produced massive hemolisis in dogs, and in no case the bilirubin was increased, demonstrating that the normal liver is capable of excreting entirely the bilirubin formed. In Monqe's Disease, the injected bilirubin showed a normal elimination, even though the initial bilirubinemia was above the admitted standard level, just as íf the excretion through the liver cells would occur at a higher threshold. These results are similar to those of Dameshek and Singer in Hemolitic Icterus. The explanation of these phenomena, may be found in a compensatory mechanism which avoid too great a loss of biliary pigments (increased urobilinogen), and keeps in the body the pirrolic nuclei used in hemoglobin resynthesis. The same hypothesis is applicable both to hemolitic Icterus and Monqe's disease. The icterus would be due neither to an hepatic cell damage, not to a relative insufficiency, but to a regulation of the basic threshold of bilirubin excretion by the hepatic cell.